KREATIVITAS GURU DALAM MEMANFAATKAN TEKNOLOGI SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MAN 1 MEDAN - Melati Maharani Nasution; Sapri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the use of technology as a medium in learning Islamic Religious Education. The focus of this research will explore the creativity of teachers in utilizing technology as a medium for learning Islamic Religious Education at MAN 1 Medan, analyzing the types of technology used, innovations in its use, and obstacles in its application. This research uses descriptive qualitative research methodology with the aim of offering a comprehensive summary of real-world, systematic, and factual circumstances and events relating to various variables, properties, and connections among phenomena. The results showed that PAI teachers at MAN 1 Medan have their own creativity and ways of utilizing technology as learning media in the form of utilizing applications such as canva, utilizing social media as a learning platform, using smart TVs to conduct presentations, and even utilizing free quiz websites and learning games.